The Factors Affecting the Quality of Earnings with Capital Structure as Intervening Variables in Banking Companies Listed on IDX - Aang Syahdina; Ghina Fadillah (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The most critical aspect in locating the value of a corporation is the great of the income generated through the corporation. Optimal earnings quality will have an effect on the value of the company which continuously shows an increase. The same thing also applies vice versa, if the quality of earnings shows results that are not optimal it will reduce the value of the company. The most important achievement when reporting earnings is that it makes it easier for stockholders and creditors to determine cash flows for future periods. Therefore, creditors and stockholders are able to predict the good and bad cash flows that will be faced in the coming period. The studies performed by the researcher has the purpose of having the ability to research the elements that have an effect on the best of profits with the capital structure used as an intervening variable withinside the banking sector this is included in the IDX list. The research that the researcher carried out made use of secondary data obtained by collecting all data on the company's financial reporting. The researchers used Purposive sampling as a data collection technique. After conducting the research and data processing, it was found that the independent board of commissioners, board of directors, managerial ownership, institutional ownership, audit committee and CSR quality had a significant effect on earnings quality with capital structure as an intervening variable both simultaneously